2014
DOI: 10.1097/mpg.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome of Home Parenteral Nutrition in Patients With Ultra‐Short Bowel Syndrome

Abstract: The survival of patients with U-SBS receiving HPN was good. Although IFALD was frequent, it had been manageable in most of the patients, but in a single complex case, it led to death. The multidisciplinary management warranted to these patients to approach the school age, to grow, and to maintain the oral intake. Patients with U-SBS are rare, and to better understand their long-term survival, further studies, including more large patient populations, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 25 publications
0
42
0
3
Order By: Relevance
“…The outcome for children is excellent as reported by the larger centres in Europe and North America,12 with 90% of children achieving independence from artificial nutrition support within 2 years and a mortality rate of <10%. Most deaths occur within the first 6 months and are due to sepsis, IFALD,11 13 and associated system abnormalities.…”
Section: When Things Go Rightmentioning
confidence: 58%
“…The outcome for children is excellent as reported by the larger centres in Europe and North America,12 with 90% of children achieving independence from artificial nutrition support within 2 years and a mortality rate of <10%. Most deaths occur within the first 6 months and are due to sepsis, IFALD,11 13 and associated system abnormalities.…”
Section: When Things Go Rightmentioning
confidence: 58%
“…who survived in good clinical condition, but in all these cases the ileocecal valve had been spared, and PN support could not be eliminated in most cases. 6,[14][15][16][17] The main factor that could explain such a successful recovery may have been, in our hypothesis, the protracted breast-feeding. Human milk plays a very positive influence on cell proliferation and on adaptive transformation of the residual intestine.…”
Section: Discussionmentioning
confidence: 97%
“…Intestinal transplantation is emerging as a potential option for these children. 34 On the other hand, Diamanti et al 35 found good quality of life in a small group of children with ultra-short bowel syndrome. Although still dependent on parenteral nutrition, the children regularly attended school and none was listed for intestinal transplantation.…”
Section: Re 1 Dealing With a Complicated And Severe Congenital Anomalymentioning
confidence: 98%
“…Although still dependent on parenteral nutrition, the children regularly attended school and none was listed for intestinal transplantation. 35 Today, intestinal transplantation for newborns with ultra-short bowel syndrome is certainly not standard practice. Cummings et al 36 asked neonatologists and pediatric surgeons whether they viewed intestinal transplant in neonates with severe short bowel syndrome as impermissible, optional, or obligatory.…”
Section: Re 1 Dealing With a Complicated And Severe Congenital Anomalymentioning
confidence: 99%